2002
DOI: 10.1161/hc0102.101776
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Characteristics of Patients With Left Atrial Thrombus and Sinus Rhythm

Abstract: Background-Left atrial (LA) thrombus is infrequently detected in the presence of sinus rhythm (SR) and, in these cases, is usually associated with additional cardiac pathologies. We sought to determine the clinical and echocardiographic characteristics of patients with LA thrombus and SR to define a high-risk group of patients prone to this uncommon clinical presentation. Methods and Results-The institution's echocardiographic laboratory database was searched to identify patients with LA thrombus, diagnosed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 31 publications
3
67
1
2
Order By: Relevance
“…In patients with major cardiac risk factors (thrombi in the left atrium, left atrial appendage and left ventricle, dilated cardiomyopathy) anticoagulation therapy is generally recommended. 2,13,14 Anticoagulation is probably even more warranted after a thromboembolic event like a TIA or stroke, although there is no evidence at this time from randomizedcontrolled trials. Recruitment for these trials would probably also be difficult because large numbers of stroke patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with major cardiac risk factors (thrombi in the left atrium, left atrial appendage and left ventricle, dilated cardiomyopathy) anticoagulation therapy is generally recommended. 2,13,14 Anticoagulation is probably even more warranted after a thromboembolic event like a TIA or stroke, although there is no evidence at this time from randomizedcontrolled trials. Recruitment for these trials would probably also be difficult because large numbers of stroke patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…LAA is a favorable site for stasis and thrombus formation, when the strength of contraction and relaxation that protects the lumen from thrombus formation is decreased [5,6]. Thrombus formation is very rare in sinus rhythm, however may still be detected in cases with high risk structural heart disease [7]. It has been reported that, left atrial thrombus formation and subsequent embolisation was less frequent in severe mitral regurgitation (MR), even in cases with AF [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors previously shown to be associated with left atrial thrombus formation (3) were absent in our patient. Severe aortic insufficiency has been implicated as an associated with a risk for left atrial thrombi in patients with sinus rhythm, due to associated left atrial stasis (3,4), with a RR for systemic embolization of 22.4 (95% CI 2.72 to 184.8) in one study (4); however, all patients in this report had at least mild mitral valve stenosis. Our patient developed acute, severe aortic insufficiency from endocarditis, which caused an acute increase in left ventricular diastolic pressure.…”
Section: Discussionmentioning
confidence: 57%